Tecnologia eletroquímica para tratamento de lixiviados de aterros sanitários - Crispim, Alana Carolyne (2023)
The majority of solid waste ends its life as sanitary waste, which causes a significant environmental impact in several aspects. In particular, rain and waste destruction in landfills result in the production of aqueous leachate containing compounds with low biodegradability, high toxicity, and a high organic load. To prevent the introduction of this toxic mixture into the environment, remedial measures are necessary. Electrochemical technologies are especially suitable for wastewater purification and contaminant reuse. Therefore, in this study, the application of electro Fenton (EF) and photo electro Fenton (FEF) processes was investigated to treat local landfill effluent with high conductivity (k = 15.8 mS cm-1) and high organic content (carbon total organic (TOC) = 1220 mg L-1). Specifically, a flow cell containing a boron-doped diamond (BDD) anode and a carbon felt (CF) cathode was developed to evaluate the effects of applied current density (30, 60 or 90 mA cm-2), production of H2O2, and the source of UV radiation (UVC or UVA) on the chemical oxygen demand (COD) of the effluent. Furthermore, acetic and formic absorption (final organic by-products of effluent degradation) as well as inorganic ion concentrations (Cl-, NO2-, NO3-, NH4+ and PO4 3-) were considered. Maximum effluent degradation and mineralization were progressive with increasing applied current density, at which more than 90% of the total organic carbon (TOC) was removed after 240 min of PEF UVC with the BDD anode at 90 mA cm-2. Therefore, EF and PEF are efficient and effective solutions for the remediation of organic pollutants in landfill effluents, especially when using the BDD anode. The integration of technologies for wastewater treatment can significantly increase the degradation efficiency of organic compounds as well as make electrochemical technologies a sustainable alternative through the use of renewable energy for the treatment of sanitary waste leachate in low-income countries.